Castleman's disease of the spleen. Issue 3 (4th May 2017) - Mantas, Dimitrios; Damaskos, Christos; Dailiani, Panagiota; Samarkos, Michael; Korkolopoulou, Penelope
Abstract: Introduction: Castleman's disease (CD), also known as giant or angiofolicular lymphoid hyperplasia or lymphoid hamartoma, is a group of atypical lymphoproliferative disorders that share common lymph node histological features and may be localized either to a single lymph node (unicentric) or occur systemically (multicentric). Patient and Method: Herein, we present a rare case of a of 75-year-old female patient who was referred to our department and after a thorough work-up, underwent splenectomy with synchronous resection of an accessory spleen, splenic artery lymph nodes, and splenic hilar lymph nodes due to splenic involvement in a multicentric CD. Results: The pathology of the specimens led to the conclusion that it was a case of polycentric HHV-8-positive CD, affecting the spleen, the accessory spleen, and the lymph nodes. Conclusions: Incidence of this rare condition is believed to be approximately 0.001–0.05%. CD has been linked to the human immunodeficiency virus (HIV), human herpes virus 8 (HHV-8), and is associated with malignancies. The pathogenesis mechanism is considered to be a dysregulation and hypersecretion of cytokines, either idiopathic or secondary to a viral infection, with the latter considered the most frequent. Solid organ involvement is very rare as is splenic involvement.